Association of ambient temperature and diurnal temperature range with the outcome of in vitro fertilization in women from Hubei, China: A retrospective cohort study - Cheng, Guan; Qu, Rui; Song, Ge; Li, Xing; Zhang, Feng; Wang, Jingxuan; Li, Wenzhu; Wen, Jiahui; Xiao, Yanfei; Wei, Yiqiu; Zhang, Weiqian; Yi, Xiaofang; et al. (Environmental research, 2024)
To examine the relationship between ambient temperature and DTR and pregnancy outcomes in vitro fertilization/intracytoplasmic monosperm injection and embryo transfer (IVF/ICSI-ET) women. The study included 5264 women who were treated with IVF/ICSI-ET at two centers in Hubei province from 2017 to 2022. The daily mean, daily maximum, and daily minimum temperatures at the subjects' home addresses were extracted, and DTR values were calculated based on latter two. The associations between ambient temperature and DTR with clinical pregnancy and live birth rates were assessed using multivariate logistic regression models adjusted for covariates. Subgroup analyses were also conducted to explore potential modifiers. High/low temperatures as well as a larger DTR had a significant effect on pregnancy outcomes in fresh cycles, but not in FET cycles. Specifically, hot weather exposure to high temperatures was associated with reduced clinical pregnancy rates: Period 4 (embryo transfer to serum HCG testing) (aOR = 0.873, 95%CI: 0.763–0.999). Ambient temperature in cold weather was positively associated with live birth rate: Period 2 (Gn initiation to oocyte retrieval) (aOR = 1.082, 95% CI: 1.01–1.170), Period 3 (oocyte retrieval to embryo transfer) (aOR = 1.111, 95% CI: 1.019–1.212), Period 4 (aOR = 1.134, 95% CI: 1.028–1.252), and Period 7 (85 days prior to oocyte retrieval to serum hCG testing) (aOR = 1.105, 95% CI: 1.007–1.212). For DTR, exposure to larger DTR (Q3) at Period 2, Period 3, and Period 6 (Gn initiation to embryo transfer) reduces clinical pregnancy and live birth rates compared with Q1. Subgroup analyses revealed susceptibility profiles across age groups and residential address populations in different sensitivity windows. Our study shows that exposure to hot and cold weather and higher DTR reduces clinical pregnancy rates and live birth rates in women undergoing fresh embryo transfer, but has no significant effect on FET cycles. [Display omitted] •High temperature exposure reduces clinical pregnancy rates in fresh embryo cycles.•Exposure to low temperatures reduces live birth rates in fresh embryo cycles.•Large diurnal temperature differences have a significant effect on pregnancy outcomes in fresh embryo cycles.•Ambient and diurnal temperatures had no significant effect on frozen-thawed transfers.